Fibrillin-1 Mutations Causing Weill-Marchesani Syndrome and Acromicric and Geleophysic Dysplasias Disrupt Heparan Sulfate Interactions - Cain, Stuart A.; McGovern, Amanda; Baldwin, Andrew K.; Baldock, Clair; Kielty, Cay M. (PLOS ONE, 2012)
The extracellular glycoprotein fibrillin-1 forms microfibrils that act as the template for elastic fibers. Most mutations in fibrillin-1 cause Marfan syndrome with severe cardiovascular and ocular symptoms, and tall stature. This is in contrast to mutations within a heparin-binding TB domain (TB5), which is downstream of the arg-gly-asp cell adhesion domain, which can cause Weill-Marchesani syndrome (WMS) or Acromicric (AD) and Geleophysic Dysplasias (GD). WMS is characterized by short limbs, joint stiffness and ocular defects, whilst fibrillin-1 AD and GD have severe short stature, joint defects and thickened skin. We previously showed that TB5 binds heparin. Here, we show that the corresponding region of fibrillin-2 binds heparin very poorly, highlighting a novel functional difference between the two isoforms. This finding enabled us to map heparin/heparan sulfate binding to two sites on fibrillin-1 TB5 using a mutagenesis approach. Once these sites were mapped, we were able to investigate whether disease-causing mutations in this domain disrupt binding to HS. We show that a WMS deletion mutant, and five AD and GD point mutants all have disrupted heparin binding to TB5. These data provide insights into the biology of fibrillins and the pathologies of WMS, AD and GD.